The Quality of Stallion Semen in Skim Milk and Dimitropoulos Extenders Preserved at 5 oC and Ambient Temperature Supplemented with Different Sugar - R I Arifiantini; B Purwantara; T L Yusuf; D Sajuthi (Faculty of Animal Science, Bogor Agricultural University, 2013)
This study was conducted to evaluate the effects of sugars supplementation in skim milk based (SM) and dimitropoulos (DV) extenders on the sperm motility and viability in stallion semen storage at 5 oC and ambient temperature (24-29 oC). Semen samples were collected from 3 stallions; evaluate individually and each of them divided into 8 aliquots. Four out of eight aliquots were diluted 1:1 with SM, while the remaining four were diluted 1:1 with DV; all were then centrifuged at 1006 g (3000 RPM) for 15 min. The supernatants were discarded, and each pellet was re-diluted with SM (control), SM trehalose (SMT), SM-raffinose (SMR), SM-fructose (SMF), DV (control), DV-trehalose (DVT), DV-raffinose (DVR), and DV-fructose (DVF). The diluted semen were divided into 2 aliquots and stored at 5 oC or ambient temperature. The sperm motility and viability were evaluated every 3 h on chilled semen stored at ambient temperature, and every 12 h on those stored at 5 oC. Results of the experiments demonstrated that sperm motility and viability in DV extender significantly higher (P < 0.05) in both temperature. The supplementation of fructose was the best on the motility and viability of the sperm at both temperatures compare to trehalose, raffinose, or the control group. The best extender and sugar combination was DVF, which the total motile sperm stored at 5 oC for 96 h was 45.1% followed by to DVT (40.2%) and DVR (39.2%). The sperm motility in DV and SMF were 35.3% and 35.6%, respectively; these were higher than those diluted with control (28.9%); SMT (30.3%), and SMR (29.6%). The study concluded that the supplementation of fructose in DV extender (DVF) was the best combination to preserve stallion sperm motility and viability stored at 5 oC or ambient temperature.